A novel tactile sensor based on structured light - Yu, Yuanlong; Xue, Hongxiang; Liang, Zhenzhen (2019 IEEE International Conference on Robotics and Biomimetics (ROBIO), 2019)
In this paper, we have developed a tactile sensor based on the working principle of structured light. It solves the problem that structured light systems are highly susceptible to ambient light and require frequent calibration. And the structural light principle is applied to the robot operation process, that the robot can acquire the three-dimensional structure information of the object during the operation process, without worrying that the robot will block the camera and affect the reconstruction effect during the robot operation. The main components of the tactile sensor are two cameras, a transparent elastomer, and an adhesion layer pattern. In the experiment, we used the sensor to reconstruct a roman column model in three dimensions, in which the adhesion layer pattern is a structured light pattern coded by the spatial coding method. The results show that the tactile sensor developed in this paper can be used for three-dimensional reconstruction of contact objects with good results. The 3D reconstruction accuracy of the sensor designed in this paper is 0.4mm.